Berberine ameliorates septic cardiomyopathy through protecting mitochondria and upregulating Notch1 signaling in cardiomyocytes - Shen, Qi; Yuan, Yufan; Li, Zelin; Ling, Ying; Wang, Jian; Gao, Mingjing; Wang, Peng; Li, Mengli; Lai, Lizhong; Jin, Jinlan (Frontiers in Pharmacology, 2024)
Septic cardiomyopathy (SCM) arises as a consequence of sepsis-associated cardiovascular dysfunction, for which there is currently no specific targeted therapy available. Previous studies have demonstrated the beneficial therapeutic effect of berberine (BBR) on SCM; however, the underlying mechanisms of action remain unclear. The objective of this is to elucidate how BBR alleviates SCM. septic cardiomyopathy rat model was established by performing cecal ligation and puncture (CLP), while a cardiomyocyte injury model was provoked in H9C2 cells using lipopolysaccharide (LPS). Cardiac function was assessed through echocardiography, and myocardial histopathology was examined with hematoxylin-eosin (HE) staining. Cardiomyocyte viability was determined through Cell Counting Kit-8 (CCK8) assay, and measurement of ATP levels was done with an ATP assay kit. Mitochondrial ultrastructure was observed using transmission electron microscopy. Real-time polymerase chain reaction (RT-PCR) and Western blotting were employed to analyze the expression of Notch1 signaling pathway components and downstream molecules in myocardial tissues and cells. In vivo, BBR markedly improved symptoms and cardiac function in SCM rats, leading to enhanced ATP content, and ameliorated mitochondrial structure. Additionally, BBR increased Notch1 protein expression in myocardial tissue of the rats. In vitro, BBR elevated the survival rates of H9C2 cell, improved mitochondrial morphology, and raised ATP levels. The mRNA expression of Notch1, Hes1, and Hes2, and Notch1 protein expression was upregulated by BBR. While these effects were reversed upon inhibiting the Notch1 signaling pathway. BBR improves septic cardiomyopathy by modulating Notch1 signaling to protect myocardial mitochondria.